Flood Hazard Map Of Sungai Kulim Using High Percentage Of Overlapping Images Captured By (UAV) Drone - Ghani, Ahmad Danial Kahfi (Universiti Sains Malaysia, 2018)
Sungai Kulim is the main river that flows through the town of Kulim in southern Kedah. It flows largely in a northwesterly direction to empty into the Perai River on the Seberang Perai. In 2017, flood occurred in downstream area of Sungai Kulim. This phenomenon probably due to high intensity of rainfall caused the uncontrollable amount of water discharge from upstream of Sungai Kulim. Impacts of that flood, nearly 100 houses located at the low-lying areas were destroyed or under water and the local residents were urged to move to the relief centre. Thus, study on various average water discharge based on return period of 2, 3, 5, 10, 25, 50, 100, and 200 years along 5 km length and 200 m width downstream river was conducted. The Unmanned Aerial Vehicle (UAV) Drone was used to capture the orthophoto of river in high percentage overlapping images. The main objective in this study is to simulate the flood extent using Hydraulic Engineering Center’s River Analysis System (HEC-RAS) software which is constructed by US Army Corp. HEC-RAS software was used to aid in channel flow analysis and flood water level determination by researchers around the world. The flood water level can helps evaluate effect of the downstream area due to average rainfall intensity. Using Digital Elevation Model (DEM) generated by Agisoft Photoscan software, HEC-RAS will simulate the area of flood probably occurred. The amount of water discharge used in the simulation were 44.25, 50.58, 57.59, 66.42, 77.58, 85.86, 94.08, and 102.27 m3/s. The water discharge were based on return period of 2, 3, 5, 10, 25, 50, 100, and 200 years. As a result, maximum velocity, maximum depth, arrival time and inundation boundary maps were produced. This finding was able to produce flood hazard map and predict risk area of flooding. This study also helped authorities to construct the emergency plan as to prevent flood occur in downstream area of Sungai Kulim. Besides, this study can give awareness to local residents of risk area on flood.